Acceptability, appropriateness, and feasibility of an online facilitation training program designed to support the implementation of person-centered care in Swedish healthcare—a qualitative study - Ewa Carlsson Lalloo; Anna Bergström; Leif Eriksson; Lars Wallin; Emmelie Barenfeld (Implementation Science Communications)
Abstract Background Despite legislative support, PCC is not systematically practiced. An online facilitation training program targeting healthcare staff was developed in Sweden. This study aims to explore the acceptability, appropriateness, and feasibility of this facilitation training program, designed to support PCC implementation. Methods This interview study evaluates the FaciLitating Implementation of Person-centered care (FLIP) training program according to the implementation outcomes acceptability, appropriateness, and feasibility, using deductive qualitative content analysis. FLIP integrates the Building Implementation Capacity for Facilitation (BIC-F), which focuses on behavioral change, and PCC principles. FLIP included workshops and supervision sessions held online, led by external facilitators. Between these meetings, the FLIP participants worked with implementation plans in co-creation with their colleagues. Five healthcare units, with different healthcare contexts, in Sweden, participated over 12 weeks with two healthcare staff assigned the role as internal facilitators per unit, selected and supported by their managers. All internal facilitators, managers, and external facilitators were invited to participate in evaluating FLIP. A total of 17 participants, eight internal facilitators, five managers, and four external facilitators were interviewed in semi-structured individual and group interviews. Results FLIP was generally accepted among all participants, due to its emphasis on PCC, comprehensive content, and clear structure, as well as its blend of training, collaboration, and mutual support. Nevertheless, the acceptability was negatively affected by low attendance, low engagement due to the online format, and initial struggles with the systematic implementation model. The systematic implementation model used in FLIP was perceived as appropriate for implementing PCC in clinical practice; however, the training on PCC was viewed as insufficient, leading to challenges operationalizing PCC elements. The participants’ perceptions of FLIP’s feasibility varied; while delivery was manageable, busy schedules and technical disruptions negatively affected attendance and engagement. Conclusions Becoming a facilitator capable of supporting the implementation of PCC is demanding and requires an understanding of both implementation and PCC. The BIC-F model was found to be accepted and appropriate, but operationalizing PCC requires more focus. Managerial support is needed to increase feasibility. Further research is required to evaluate whether facilitation skills can be trained online for large-scale PCC implementation.